More matches, less time: how load ratios reveal gaps between training and competition in football - Galiano, C.; Nakamura, F. Y.; Ribeiro, J.; Asín-Izquierdo, I.; Asian-Clemente, J. A. (The Journal of Strength and Conditioning Research, 2026)
The aim of this study was to analyze the external load ratios of professional football players across microcycles of different lengths and to compare the distribution of external load in each of these types of microcycles. Twenty-eight professional outfield soccer players were monitored daily using GPS for 2 seasons (2022/2023 to 2023/2024). Players participated in a total of 105 matches (regular season: 68, European competition: 20, national cup: 17) throughout the 2 analyzed seasons. Total distance, high-speed running (HSR), sprinting distance, number of sprints, and the number of accelerations/decelerations >3 m·s-2 were recorded during both training sessions and matches. Microcycles of 3, 4, 5, and 6 days were analyzed. An individual training-to-match ratio was calculated for each external load measure in each microcycle. All external load ratios showed differences across microcycle lengths (p < 0.001; Eta2p > 0.364) with larger ratio values for longer microcycle durations. Regardless of the microcycle duration, accelerations >3 m·s-2 showed higher values than the other variables (p < 0.013; ES > 0.29), while those related to high-speed activity displayed lower values than the rest (p < 0.001; ES > 0.37). This "overstimulation" of accelerations >3 m·s-2 shows greater differences than the other variables as the microcycle lengthens. This insight can guide coaches in optimizing training periodization, ensuring a better balance between undervalued and overvalued variables, particularly for HSR and sprint performance in different microcycle structures.